PENGARUH MEDIA TERHADAP BUDAYA YANG BERKEMBANG DI MASYARAKAT - Anggriani Alamsyah (AL TAJDID, 2009)
One of the earliest and best-known mass communication theorists is Harold Lasswell. This model outlines the basic elements of communication, the last element of which direct us to the entire outcome-research literature.